Phenotypic plasticity and ecological memory in Andropogon gerardii: responses to simulated grazing pressure - Mohammadi, Shahla (Kansas State University, 2024)
This thesis explores the effects of ecological memory on plants responses to subsequent stressors, specifically focusing on the physiological and biochemical responses of Andropogon gerardii (big bluestem) to grazing pressures. By examining the concept of ecological memory, this research highlights how past environmental stressors, such as grazing, influence future plant responses. Utilizing a multifaceted approach that spans predictive modeling, physiological assessments, and biochemical analyses, this study rigorously tests the hypothesis that the legacy effects of grazing, embodied in ecological memory, profoundly impact A. gerardii's physiological fabric and biochemical mechanisms. Structured into three chapters, the thesis first explores the biochemical and physiological foundations of stress responses, investigating the role of flavonoids and phenolic compounds in mediating A. gerardii's response to simulated grazing stress (Chapter 2). It then examines how these biochemical responses underpin post-defoliation growth and biomass allocation, revealing the echoes of ecological memory in plant growth patterns and resource allocation strategies (Chapter 3). Our findings reveal that ecological memory influences A. gerardii's response to simulated grazing, manifesting in nuanced physiological adaptations. Despite initial hypotheses, the interaction between plant memory and clipping treatments showed a complex effect on chlorophyll content and photosynthetic rates, with plants exhibiting a history of grazing demonstrating enhanced photosynthetic performance post-defoliation. Interestingly, the study underscores the significant role of flavonoids in mediating physiological responses to stress, independent of ecological memory. These secondary metabolites were pivotal in optimizing photosynthetic efficiency and gas exchange, contributing to the plant's defensive responses and recovery post-clipping. Furthermore, the research delves into biomass allocation strategies in response to defoliation, revealing that early-season biomass removal does not significantly affect end-of-season growth traits across plants with and without grazing memory. However, a notable finding was the consistent influence of relative growth rates (RGR) during early and late growth stages on end-of-season biomass, underscoring the inherent growth dynamics as a critical determinant of plant vigor. Contrary to the anticipated benefits of grazing memory on growth enhancement, the study suggests that A. gerardii's immediate physiological responses to defoliation play a more pivotal role than previously hypothesized. While grazing memory appears to confer some degree of adaptive advantage, it does not significantly modulate the correlation between RGR and end-of-season biomass attributes, indicating that innate growth responses are paramount. In conclusion, this thesis illuminates the complexity of ecological memory and its impact on the physiological and growth responses of A. gerardii to grazing. The findings highlight the crucial role of secondary metabolites, particularly flavonoids, in mediating plant responses to stress and suggest that managing the timing and intensity of defoliation may be more effective than leveraging ecological memory in grassland management practices.
Keywords: Ecological memory; Andropogon gerardii; Photosynthesis; Phenylalanine ammonia-lyase; Phenols; Flavonoids